Assessment of the radiological control at the Ipen radioisotope production facility - Janete Cristina Gonçalves Gaburo Carneiro; Matias P Sanches; Demerval L Rodrigues; Daniela Campos; Paulo R Nogueira; Sandra R Damatto; Brigitte R S Pecequilo (Brazilian Journal of Radiation Sciences, 2015)
The main objective of this work is to evaluate the 2013 annual radiological control results in the radiopharmaceuticals areas of the Nuclear and Energy Research Institute, IPEN/SP, and the environmental radiological impact, resulting from the practices there performed. The current evaluation was performed through the analysis of the results obtained from occupational and environmental monitoring with air samplers and TL dosimeters. All monitoring results were compared with the limits established by national standards. The radionuclides detected by air sampling (in activated carbon cartridges and filter paper) at the workplace during radioisotope production were 131I, 99mTc and 99Mo, with activities concentrations values below the annual limits values. For the radioactive gaseous releases (Bq/m3), the activities concentrations also remained below the maximum admissible values, excepting to 125I release due to an unusual event occurred in a researcher laboratory, but the radiological impact to environmental was no significant. The occupational monitoring assessment was confirmed by the Environmental Radiological Monitoring Program results with air samplers and TL dosimeters. The mean annual background radiation at IPEN in 2013, according to the Environmental Radiological Monitoring Program results was 1.06 mSv. y -1, below the ICRP 103 recommended limit of 20 mSv.y-1 for workers.